The Emerging Trend of Narration in Pakistani Ads - Ahmad Bilal (بازیافت, 2017)
Television commercials are generally produced in two different  styles: in argumentative manner, and in narrative style. In argumentative style various attributes of the product are shown in a logical manner; whilst narrative style is more towards storytelling and product is presented as a part of the story. Generally around the globe, and particularly in Pakistan argumentative style has always been in fashion. Particularly in the earlier years advertisements are considered to be a logical way to present the  key characteristics of a product to its consumers. Mostly, this straight forward approach is because advertising is still at its infancy in Pakistan; however, in the last five years, a shift from the argumentative to narrative can be observed. This research paper reviews the some of the television advertisements, and examines these to study the shift in the trends of advertisements.